Development of Inquiry-Based Student Worksheet on the Phylum Platyhelminthes, Nemathelmintes, and Annelida Materials - Citraningrum, Mivtha; Sanjaya, Yayan; Sudargo, Fransisca; Riandi, Riandi; Rakhmawati, Ismi; Haka, Nukhbatul Bidayati (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
This study aims to develop student worksheets on Vermes (worms). The research method employed is Research and Development with the 4D development model consisting of four stages: defining (Define), designing (Design), developing (Develop), and disseminating (Disseminate). The study results indicate that the student worksheet developed is feasible based on the validation results by three experts in media, material, and language. It can be concluded that the worksheet of Phylum Platyhelminthes, Nemathelmintes and Annelida is feasible to be used as a new learning resource. It is recommended that further research focus on implementation to analyze the effectiveness of these worksheets in improving students' reflective thinking skills. Pengembangan Lembar Kerja Mahasiswa (LKM) Berbasis Inkuiri Pada Materi Filum Platyhelminthes, Nemathelmintes Dan Annelida ABSTRAK: Penelitian ini bertujuan untuk mengembangkan Lembar kerja mahasiswa pada materi Vermes (Cacing). Metode penelitian yang digunakan adalah Reseach and Development dengan model pengembangan 4D terdiri atas pendefinisian (Define), perancangan (Design), pengembangan (Develop), dan penyebaran (Disseminate). Hasil penelitian menunjukkan bahwa Lembar kerja mahasiswa yang telah dibuat layak dikembangkan berdasarkan hasil validasi tiga ahli (media, materi dan bahasa). Dapat disimpulkan bahwa Lembar Kerja Mahasiswa yang memaparkan materi Filum Platyhelminthes, Nemathelmintes dan Annelida layak digunakan sebagai sumber belajar baru. Rekomendasi yang diberikan untuk penelitian selanjutnya adalah implementasi untuk melihat seberapa besar efektifitas sumber belajar ini dalam meningkatkan kemampuan berpikir reflektif mahasiswa.